Applications of shallow seismic refraction measurements in the Western Carpathians (Slovakia): case studies - BRIXOVÁ, Bibiana; MOSNÁ, Andrea; PUTIŠKA, René (Contributions to Geophysics and Geodesy, 2018)
Shallow seismic measurement, specifically seismic refraction tomography, is an effective geophysical method that has applications in various sectors. It enables the search for and determination of the course of the interfaces, thus helping to resolve geological, environmental, hydrogeological, engineering, geotechnical and other problems. The paper demonstrates the possibilities of using these methods through examples of shallow seismic measurements that have been performed at various four locations in the Western Carpathian Mountains. The first case study describes Monastery Pond at Katarínka. It was found that, the basement of the Monastery pond is at a depth of 2–3 m below the surface and the results were also confirmed by electrical resistivity tomography (ERT). The next measurement through the thermal power station waste storage showed that the storage area base runs at a depth of about 20 m under the measured profile. The third case study addresses the depth of groundwater depth in the area of Borská nížina. The measurement confirmed the assumed depth of ground water level at 3.35 m below the surface. In the last case study, border fault between the Turiec Basin and the Malá Fatra Mts. was mapped by application of shallow refraction methods. The results show that shallow seismic methods shed light on the problem and in combination with other geophysical methods are an effective tool with great potential. They provide very useful data for shallow mapping applications.